Applying COBIT 2019 to Design a Tailored IT Governance System for PT. Telekomunikasi Seluler Manado Branch - Joe Yuan Mambu; Toetik Wulyatiningsih; Stenly Adam (Jurnal Informasi dan Teknologi, 2024)
This study evaluates IT governance at PT. Telkomsel Manado using the COBIT 2019 framework. The main issue is how to enhance IT performance and manage risks more effectively. The research methodology includes a literature review and stakeholder interviews to gather data on the company's IT strategy, goals, risks, and challenges. The findings indicate that the implementation of COBIT 2019 provides a comprehensive assessment of the company's IT governance. The IT audit revealed several areas needing improvement, particularly in risk management and aligning IT strategy with business objectives. Based on these findings, recommendations are made to optimize IT utilization to improve operational efficiency and effectiveness. The study shows that PT. Telkomsel Manado has 7 core models with capability level 4, including EDM03, APO12, BAI03, BAI06, DSS04, DSS05, and MEA03. In conclusion, adopting the COBIT 2019 framework can enhance IT performance and efficiency, assisting PT. Telkomsel Manado in addressing their technological and business challenges.